Leadership as One of the Important Characteristics of Social Activity in Higher Education Students - Kadirov Hasanboy Oribjonovich (Researchparks Publishing, 2023)
the article describes the rise of youth leaders in higher education in increasing the social activity of today's young workers and forming competitive leaders